Pengaruh Penambahan Puree Ubi Jalar Ungu (Ipomoea batatas L. var. Ayamurasaki) Terhadap Karakteristik Yoghurt Santan - Dewi, Ni Made Arini Santi; Suparthana, I Putu; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i04.p09, 2024)
Coconut milk yoghurt is yoghurt made from coconut milk fermented by lactic acid bacteria (LAB). Generally, coconut milk yoghurt has a less thick texture and less antioxidant. Purple sweet potato, a food rich in carbohydrates and antioxidant, can be utilized to enhance the nutritional value and sensory quality of coconut milk yoghurt.This study aimed to determine the effect of adding purple sweet potato puree on the characteristics of coconut milk yoghurt and to find out the addition of purple sweet potato puree to produce coconut milk yoghurt with the best characteristics. This research used a Completely Randomized Design (CRD) with 5 treatment levels adding 0 percent, 5 percent, 10 percent, 15 percent and 20 percent purple sweet potato puree. This treatment was repeated three times, resulting in a total of 15 experimental units. The data obtained were analyzed statistically using ANOVA (Analysis of Variance) and if the treatment had an effect on the observed parameters (P<0,05), the Duncan Multiple Range Test was carried out. The research results showed that the addition of purple sweet potato puree had a significant effect (P<0,05) on pH, total lactic acid bacteria, protein content, viscosity, antioxidant activity, sensory color, aroma, texture, taste and overall acceptability of coconut milk yoghurt. The treatment with the addition of 20 percent purple sweet potato puree produced coconut milk yoghurt with the best characteristics: pH 4,33, total LAB 4,4 x 108 cfu/ml, protein content 4 ,40 percent, viscosity 2666,67 mPa.s, antioxidant activity 77,47 percent, overall preferred attributes for color, aroma, texture, taste, and overall acceptance, with the criteria of purple color, thick texture and sour taste. Keywords: characteristics, purple sweet potato puree, coconut milk yoghurt